2015
DOI: 10.1038/onc.2015.10
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke mediates epigenetic repression of miR-217 during esophageal adenocarcinogenesis

Abstract: Although microRNAs (miRs) have been implicated in the pathogenesis of various human malignancies, limited information is available regarding mechanisms by which these noncoding RNAs contribute to initiation and progression of tobacco-induced esophageal cancers. In this study, array and quantitative reverse transcriptase-PCR techniques were used to examine miR expression in immortalized esophageal epithelia (IEE) and esophageal adenocarcinoma (EAC) cells cultured in normal media with or without cigarette smoke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…MiR-17 encodes seven mature miRs, and several studies have revealed their involvement in cancer [20, 21]. Multiple studies have focused on investigating the role of in oral cancer [22, 23]. The overexpression of oncogenic miR may reduce the protein products of tumor-suppressor genes.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-17 encodes seven mature miRs, and several studies have revealed their involvement in cancer [20, 21]. Multiple studies have focused on investigating the role of in oral cancer [22, 23]. The overexpression of oncogenic miR may reduce the protein products of tumor-suppressor genes.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs have been documented to be involved in various biological processes, including tumorigenesis through the regulation of cell proliferation, apoptosis, differentiation, migration, invasion, epithelial-mesenchymal transition and chemoresistant phenotype formation (5)(6)(7)(8)(9)(10)(11). Several previous studies have reported that miR-149 serves crucial roles in the progression of various tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have suggested that KLK7 acts as a proliferative factor in a number of cancer types (Kryza et al ., ; Stefanini et al ., ; Walker et al ., ; Xi et al ., ), in the M74‐D6 and M74‐H melanoma cell lines, KLK7 overexpression surprisingly suppressed cell growth compared to M74‐mock cells (Fig. A).…”
Section: Resultsmentioning
confidence: 78%